Take care of the living : reconstructing Confederate veteran families in Virginia - McClurken, Jeffrey W., 1973- (Nation divided., 2009)
Using letters, diaries, church minutes, and military and state records, as well as close analysis of the entire 1860 and 1870 Pittsylvania County manuscript population census, McClurken explores the consequences of the war for over three thousand Confederate soldiers and their families. --from publisher description.